DETERMINATION OF ACUTE TOXICITY OF OINTMENT WITH PINUS SYLVESTRIS EXTRACT - Mandziy, T.P.; Popadynets, O.H.; Hrytsyk, A.R. (World of Medicine and Biology, 2020)
The necessity of search for new biologically active substances among the medicinal plants of Pinus species does not cause any doubts in it. Promising outlook of Pinus sylvestris application is confirmed by many publications of both domestic and foreign researchers. Post the performed study it is known that the obtained dry extract is practically non-toxic and has a wide range of biological effects. One of the main priorities of the new dosage form implementation is its low toxicity. Therefore, purposeful technology of ointment based on dry extract and controlled trial of acute toxicity are the priorities in the pharmacological studies. The purpose of the work was to study the acute toxicity of the ointment based of the Pinus sylvestris dry extract, which was first performed. The acute toxicity was studied on white mice with a single oral administration of the drug. The mice were observed for 14 days. The animals’ general condition, mortality, body mass dynamics before and after the experiment were studied. Macroscopic assessment of the internal organs status was performed and their histological structure was studied. As studies have shown, after oral administration of the ointment with the Pinus sylvestris extract in the dose of 0.5 ml, signs of toxicity in mice were not revealed. According to the classification by K. K. Sidorov, the ointment with the Pinus sylvestris extract belongs to practically non-toxic compounds. Thus, the ointment with Pinus sylvestris extract belongs to the fifth class - practically non-toxic when administered orally.